Stress and psychological trauma as predictors of cancer-related fatigue in breast cancer patients (SaFE study)—study protocol of a prospective follow-up study - Hofmann, Hanna; Koch, Thorsten; Brucker, Cosima; Radermacher, Peter; Müller, Markus; Waller, Christiane; Stein, Barbara (Frontiers in Psychology, 2025)
IntroductionCancer-related fatigue (CRF) is a common symptom of cancer and/or its treatment. Most cancer patients are affected during treatment, as well as years thereafter. Around a third of survivors report suffering from CRF. Those affected are often restricted in their everyday life. Acute and chronic stress are factors that increase a person’s vulnerability to develop CRF. In previous studies different instruments measuring acute and chronic stress related to CRF were used. However, a global instrument to determine individual stress load is lacking.MethodsTherefore, a developed global stress index (GSI) combining specific measuring instruments for acute and chronic stress is validated on an oncological sample and its influence on fatigue is examined. It is hypothesized that individuals with a high global stress load measured by the GSI report higher levels of CRF. The data will be collected using questionnaires in participants suffering from breast cancer with a curative treatment approach. Participants will be surveyed during tumor-specific therapy and six months later. They receive a consultation if fatigue symptoms are strongly pronounced. The study is registered at Deutsches Register Klinischer Studien, no. DRKS DRKS00027864.DiscussionThis will be the first study using the GSI as a valid measure for surveying longitudinally acute and chronic stress load in an oncological sample in relation to CRF symptom development. The GSI may help to identify tumor patients with high levels of stress in good time and thus prevent chronic fatigue.